Предмет: Алгебра, автор: Чужой1979

∫x^2/(2*x^2+1)dx = ∫(1/2−1/2*(1/(2*x^2+1)dx как это получается

Ответы

Автор ответа: DariosI
0
 intlimits{ frac{ x^{2} }{2 x^{2} +1} } , dx = intlimits{ frac{  frac{1}{2}* 2x^{2} }{2 x^{2} +1} } , dx=intlimits{ frac{  2x^{2} }{2(2 x^{2} +1)}} , dx=intlimits{ frac{  (2x^{2}+1)-1 }{2(2 x^{2} +1)}} , dx= \  \ intlimits{( frac{  2x^{2}+1}{2(2 x^{2} +1)}- frac{1}{2(2 x^{2} +1)}) } , dx=intlimits{ (frac{1}{2} - frac{1}{2} *frac{1}{(2 x^{2} +1)}) } , dx= \  \   intlimits{ frac{1}{2} } , dx+ frac{1}{2}   intlimits { frac{1}{2 x^{2}+1 } } , dx
Похожие вопросы